SEED GERMINATION PLASTICITY OF TWO ENDANGERED SPECIES OF FERULA IN THE CONTEXT OF CLIMATE CHANGE - Shanjani, Parvin Salehi; Mousavi, Amir; Farsad, Faeze Rasoulzadeh (Plant Breeding and Seed Science, 2020)
Ferula assa-foetida and F. gummosa, Apiaceae, are important endemic and endangered medicinal plants. Survival of the species is threatened by climate change, overexploiting (as source of oleo-gum resin and for-age) and lack of organized cultivation. Cultivation of these valuable medicinal plants is restricted by insuffi-cient domestication knowledge. Germination characteristics of different populations of Ferula taxa were studied with the aim of describing and comparing their responses to continuous cold stratification condition. Germination cues for the species were complex, with dormancy mechanisms present to restrict germination until cold stratification are fulfilled. Results indicated that a period of 4 weeks of stratification is sufficient for germination of F. assa-foetida, but optimal germination of F. gummosa require stratification for periods of 8 weeks. Both species were able to germinate at very low temperatures (4°C). Within-taxon differences in dor-mancy breaking and seedling emergence may interpret as local adaptations. The continued regeneration and propagation of the species in the wild will depend on the temperature and moisture status of the soil during winter and the maintenance of conditions suitable for stratification for an appropriate length of time.